Key to the New World : a history of early colonial Cuba - Martínez-Fernández, Luis, 1960- (University of Florida Press, 2018)
This book is the first English-language comprehensive history of early colonial Cuba published in the last 100 years. It is divided into eight chapters that cover a range of topics from the island's geological formation up to 1700: geography, indigenous inhabitants, first encounters between Europeans and Amerindians, otherwise known as the discovery of the New World, the conquest and colonization of Cuba, demographic realities such as race, gender and social structure, and cultural developments such as transculturation, piracy and other forms of aggression, and slavery and sugar production.